Pathogenic Potential of Erysipelothrix piscisicarius in Pigs and Its Implications for Surveillance in Brazil - Petri, Fernando Moreira [UNESP]; da Silva Nogueira, Giovana [UNESP]; Simão, Gustavo M. R.; Panneitz, Ana K. [UNESP]; de Aguiar, Gabriel A. [UNESP]; de Lima, Ana Clara A. [UNESP]; Braga, Eduarda R. [UNESP]; do Carmo, Kellem; Kuchiishi, Suzana S.; Reis, Adrienny T.; Vannucci, Fabio A.; de Oliveira, Luís Guilherme [UNESP] (Wiley, 2025)
Erysipelothrix (E.) piscisicarius is an emerging pathogen previously described in fish and more recently isolated from a clinical outbreak in swine. This study aimed to evaluate the course of infection and pathological outcomes of E. piscisicarius in pigs using an experimental intradermal challenge model. Twenty-six 70-day-old pigs were randomly allocated into three groups: high-dose (HD group, n = 10) and low-dose (LD group, n = 10) were challenged intradermally with 1010 colony forming units (CFUs) and 108 CFU using a Brazilian field isolate obtained from a pig with erysipelas-like lesions and confirmed by whole-genome sequencing (WGS) and average nucleotide identity (ANI), respectively, while CONT (control, n = 6) served as a negative control. Clinical monitoring, hematological assessments, acute-phase proteins (APPs) quantification, bacteriological culture, and quantitative PCR (qPCR) targeting the spaC gene were performed over 14 days. Challenged pigs developed mild clinical signs, including transient fever and characteristic rhomboid skin lesions resembling classical swine erysipelas. No mortality occurred. Hematological analysis revealed significant reductions in red blood cell (RBC) count, hemoglobin (HGB), and hematocrit (HCT), particularly in the LD group at 7 and 14 days post-challenge (dpc) (p  < 0.05), suggestive of inflammatory anemia. APP analysis showed a significant increase in ceruloplasmin across all groups over time, whereas transferrin levels decreased only in the control group. Bacterial isolation was unsuccessful; however, qPCR detected E. piscisicarius deoxyribonucleic acid (DNA) in blood, skin, liver, and spleen samples, confirming systemic dissemination, particularly at 7 dpc. These findings demonstrate that E. piscisicarius can induce clinical and pathological alterations in swine, although with mild severity under experimental conditions. Moreover, the study highlights the importance of differentiating E. piscisicarius from E. rhusiopathiae in diagnostics, given the potential limitations of current vaccine strategies.